(untitled) (Research, Society and Development, 2023)
Nuclear Medicine is a diagnostic method that integrates radioactive substances such as Sodium Pertechnetate (Technetium=TC ⁹⁹m) and Iodine-131. Nuclear Medicine, Forensic Medicine or molecules marked with the radioisotope Sodium Pertechnetate, associated with drugs, contribute to Forensic Science. Therefore, as the energetic aspect influences the human organism, the present study aims to describe the interrelationships between Nuclear Medicine, Legal Medicine and Quantum Physics and their applications to Forensic Sciences. Thus, the literature review study with a systematic approach was conducted in June 2023, from the following databases: Virtual Health Library (VHL) and Publisher Medline (PubMed), obtaining 11 scientific articles. Therefore, it was found that the diagnosis of brain death and vegetative stage, based on imaging tests such as Cerebral Scintigraphy, contributes to legal parameters associated with organ donation for therapeutic purposes, which requires family authorization of the patient who died. Brain waves can be linked to fundamentals of quantum physics. Therefore, the energy aspect can influence therapies, disease detection and consequently the human body. However, the relevance of Nuclear Medicine in the diagnosis and treatment of diseases was verified, which is associated with Legal Medicine and Forensic Sciences.